2021
DOI: 10.3390/biom11091273
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of SARS-CoV-2 RBD May Alter Its Molecular Structure to Improve Its Infection Efficiency

Abstract: The receptor-binding domain (RBD) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mediates the viral–host interaction and is a target for most neutralizing antibodies. Nevertheless, SARS-CoV-2 RBD mutations pose a threat due to their role in host cell entry via the human angiotensin-converting enzyme 2 receptor that might strengthen SARS-CoV-2 infectivity, viral load, or resistance against neutralizing antibodies. To understand the molecular structural link between RBD mutations and infectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 63 publications
3
38
0
Order By: Relevance
“…This might suggest the requirement of a certain degree of flexibility to maintain T20′s conformation for binding to the gp41 receptor. Moreover, the solvent accessible surface area (SASA) was used to predict conformational changes in WT and mutant proteins [11][12][13]. There was a slight enhancement in the SASA of the E143A mutant compared to WT T20 (Figure 2B).…”
Section: Conformational Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…This might suggest the requirement of a certain degree of flexibility to maintain T20′s conformation for binding to the gp41 receptor. Moreover, the solvent accessible surface area (SASA) was used to predict conformational changes in WT and mutant proteins [11][12][13]. There was a slight enhancement in the SASA of the E143A mutant compared to WT T20 (Figure 2B).…”
Section: Conformational Changesmentioning
confidence: 99%
“…The free energy landscape (FEL) of the all-peptide atoms was used to evaluate conformations at minima during the MD simulations [11]. The FEL of the backbone residues was plotted by projecting MD trajectories onto the first two principal components PC1 and PC2 of T20 and the E143A mutant.…”
Section: The Free Energy Landscape (Fel)mentioning
confidence: 99%
See 2 more Smart Citations
“…Several molecular dynamics studies have demonstrated these effects and their implications for the SARS-CoV-2 variants fitness ( Alaofi and Shahid, 2021 ; Istifli et al, 2021 ; Peters et al, 2021 ). However, in most of these studies the change in the variants' fitness is demonstrated considering the combined mutations effect (or the set of them) identified in the VOCs, which limits the understanding of the effect and impact caused by each one of them individually.…”
Section: Introductionmentioning
confidence: 99%